The Prevalence of the Different Components of the Metabolic Syndrome (MetS) in Obese Nondiabetic Children and Young Adolescents and their Anthropometric Data in Relation to Parents.: Metabolic Syndrome in Obese Nondiabetic Children - Hamed, Noor; Soliman, Ashraf; De Sanctis, Vincenzo; Alaaraj, Nada; Alyafei, Fawziya; Shaat, Mona; Aljaffali, Noora; Itani, Maya; Jour, Celine (Acta Biomedica Atenei Parmensis, 2021)
In Qatar, the prevalence of metabolic syndrome (MetS) in children and adolescents is increasing in parallel with the increasing trends in obesity rates. In Qatar, the prevalence of obesity is relatively high. Aim: To assess the prevalence of the different components of MetS and plasma atherogenic indexes (AIP) in obese children and adolescents and to compare their anthropometric data with their parents (genetic background). Methodology: We analysed the anthropometric and biochemical profile of 91 randomly selected obese children and young adolescents (age: 10.5 ± 2.7 years) who attended to the Paediatric Clinic of Hamad Medical Center (HGH) in Doha (Qatar) form January 2017 to December 2019. Data recorded included: age, gender, weight and height, body mass index (BMI), systolic and diastolic blood pressures. Biochemical data including lipid profile, glycated hemoglobin (A1C), and alanine transferase level (ALT) were recorded and compared with normal lab data for the same age group. Results: Obese children had a high prevalence of dyslipidaemia, dysglycemia and non-alcoholic fatty liver disease (NAFLD). Using the modified adult MetS criteria, MetS was present in 30.2% of this obese cohort. AIP was high in 76.7% of the patients. Standing height standard deviation score (Ht-SDS) of obese children was significantly higher compared to Ht-SDS of their parents as well as to mid-parental height SDS (MPHt-SDS) (-0.37± 0.79). The BMI and BMI-SDS did not differ between obese children and their parents. Conclusion: The occurrence of MetS in 30% of our obese non-diabetic children and young adolescents pointed out to the necessity to impose early detection and preventive measures on a national scale.